Pendekatan Konseling dalam Membangun Minat Entrepreneurship Karyawan Kristen - Yeyen Darmadji (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2019)
Improving living standards is a problem that continues to roll from time to time, both with the theme of poverty alleviation or economic empowerment. In the context of the Christian world the church must provide education about the importance of people doing entrepreneurship in order to improve their economy. This article is a qualitative study with a literary approach to reflect biblically about entrepreneurship and how the church cares to do that as its responsibility. In conclusion, Christian counseling approaches can be used to encourage Christian entrepreneurship activities.